1997
DOI: 10.1021/jp962578u
|View full text |Cite
|
Sign up to set email alerts
|

Electrooptical Properties and Molecular Polarization of Iodine, I2

Abstract: Experimental and theoretical efforts are combined to determine a reliable value of the static dipole polarizability of I2. The experimental estimate of the mean dipole polarizability is α = 69.7 ± 1.8e 2 a 0 2 E h -1. The polarizability of the iodine atom has also been deduced from experimental measurements and is estimated at 32.9 ± 1.3e 2 a 0 2 E h -1. Accurate ab initio calculations predict α = 70.9 ± 1.4e 2 a 0 2 E h -1 and for the anisotropy Δα = 41.2 ± 0.8e 2 a 0 2 E h -1. The deformation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…The construction of molecule-specific, purpose-oriented basis sets for large molecular architectures or low-symmetry polyatomics is largely impractical. Nevertheless, previous work shows that for systems of reasonable size as atoms [23,53], atomic anions or cations [54,55], diatomics [56,57] and triatomics [58][59][60][61], symmetric polyatomics [62][63][64], and clusters [65][66][67][68], one can easily control the construction of the basis set in order to obtain suitable basis sets for electric property calculations.…”
Section: Electric Properties Of Atoms Molecules and Clusters Basicmentioning
confidence: 99%
“…The construction of molecule-specific, purpose-oriented basis sets for large molecular architectures or low-symmetry polyatomics is largely impractical. Nevertheless, previous work shows that for systems of reasonable size as atoms [23,53], atomic anions or cations [54,55], diatomics [56,57] and triatomics [58][59][60][61], symmetric polyatomics [62][63][64], and clusters [65][66][67][68], one can easily control the construction of the basis set in order to obtain suitable basis sets for electric property calculations.…”
Section: Electric Properties Of Atoms Molecules and Clusters Basicmentioning
confidence: 99%
“…Although the construction of purpose-oriented basis sets for polarizability calculations has been the object of several investigations [51][52][53][54][55], there are no reliable criteria for the choice of basis sets in theoretical predictions of electric hyperpolarizabilities. Previous experience shows that for atoms [56][57][58][59], diatomics [60][61][62], triatomics [63][64][65], and small polyatomics [66][67][68][69], it is possible to design basis sets by systematically augmenting reliable substrates of GTFs. Different strategies must be adopted in the case of clusters [70] or sequences of clusters [71][72][73][74].…”
Section: Computational Strategymentioning
confidence: 99%
“…[63][64][65][66] In this work, atom-specific or moleculespecific purpose-oriented basis sets are exclusively used. In previous work, it has been shown that such basis sets are easily obtained for small systems such as atoms, 67 diatomics, 65,68 triatomics, 67, 69 and small symmetrical polyatomics. 70,71 Here, only a succinct presentation of the essential characteristics of the calculations performed for the pairs H 2 -Rg (Rg = He, Ne, Ar, Kr, and Xe) is given.…”
Section: Collision-induced Polarizabilities: Computing Methodsmentioning
confidence: 99%